2016
DOI: 10.1093/infdis/jiw095
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction–Associated Transcript, a Long Noncoding RNA, Is Overexpressed During Dilated Cardiomyopathy Due to Chronic Chagas Disease

Abstract: Long noncoding RNAs (lncRNAs) modulate gene expression at the epigenetic, transcriptional, and posttranscriptional levels. Dysregulation of the lncRNA known as myocardial infarction-associated transcript (MIAT) has been associated with myocardial infarction. Chagas disease causes a severe inflammatory dilated chronic cardiomyopathy (CCC). We investigated the role of MIAT in CCC. A whole-transcriptome analysis of heart biopsy specimens and formalin-fixed, paraffin-embedded samples revealed that MIAT was overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…They identified 14 lncRNAs deregulated in these patients, such as CDKN2B-AS1/ANRIL, EGOT and H19. Additionally, Frade et al [16] performed a whole-transcriptome analysis of heart biopsy specimens of DCM patients and healthy hearts donors and revealed that MIAT was overexpressed in patients with DCM. Whereas, these lncRNAs were not identified in our study, which may be due to the sample heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They identified 14 lncRNAs deregulated in these patients, such as CDKN2B-AS1/ANRIL, EGOT and H19. Additionally, Frade et al [16] performed a whole-transcriptome analysis of heart biopsy specimens of DCM patients and healthy hearts donors and revealed that MIAT was overexpressed in patients with DCM. Whereas, these lncRNAs were not identified in our study, which may be due to the sample heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified many lncRNAs associated with diseased hearts [8][9][10]. However, there are still not enough studies on the functions of lncRNAs in DCM [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Human left ventricular free wall heart tissue samples were obtained from patients with end-stage heart failure CCC at the time of heart transplantation (n = 25). CCC patients underwent serological diagnosis of T. cruzi infection and standard electrocardiography and echocardiography, and tissues were subject to histopathological assessment [ 13 ]. Biopsies from controls (n = 7) were obtained from healthy hearts of organ donors having no suitable recipient ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, lncRNAs are recognized as additional players in cardiomyopathies (Table 3). 131,132 A recent work tested whether circulating mitochondrial lncRNAs might serve as biomarkers of cardiac remodeling in HCM patients. Two transcripts, uc004cov.4 and uc022bqu.1, were elevated in the circulation of hypertrophic obstructive cardiomyopathy patients when compared with hypertrophic nonobstructive cardiomyopathy and healthy subjects.…”
Section: Cardiomyopathymentioning
confidence: 99%